Research on Becoming an English Teacher Through Lacan’s Looking Glass - Tony Brown, Mike Dore, Christopher Hanley (2019)
Research on Becoming an English Teacher considers the process of becoming a teacher from a variety of perspectives, where the ambition is to consider how people can change themselves within that process. By pursuing an approach influenced by the psychoanalytic theory of Jacques Lacan, the authors consider practitioner research as an approach to professional and personal development, and how it might be understood as a strategy within both teaching and teacher education.